QUANTITATIVE ASSESSMENT OF CORRUPTION AND ITS PECULIARITIES - Turdikulov Shuxrat Xudoyqulovich (Journals Park Publishing, 2022)
In this article, the author focused on the problems of quantitative assessment of corruption and modeling in its bartarfing. In this he highlighted the large and small types of it, along with cases of corruption in the political, economic, social sphere. At the same time analyzed the cases in the countries of the world.
Keywords: corruption, assessment, statistical assessment, quantity analysis, bribery, extortion, corruption measurement, index